Assessment of nanofiltration efficiency for simultaneous concentration of copper and recovery of acid from highly acidic wastewater - Bencheng Hu; Haowen Wu; Wenhao Su; Keyu Yao; Li Long; Pengfei Sun; Yongcheng Wang; Lin Lin; Hao Guo; Xiao-yan Li (Water Research, 2026)

The role of arbuscular mycorrhizal fungi on ecosystem multifunctionality across phenological phases under warming in alpine meadows - Keyu Chen; Xiaoyue Yin; Luming Ding; Jingying Feng; Wubuli Subinuer; Changting Wang; Xinhua He; Chuangming Yang (CATENA, 2026)

Cross-species validation of conserved miR-504/PDHA1 and miR-500/EGLN2 interactions in sheep oocyte development - Junzheng Zhang; Jie Wang; Hao Li; Keyu Fu; Xu Han; Shuang Ji; Yi Jin (Theriogenology, 2026)

UAV-based measurements of methane emissions from two electrically-driven natural gas compressor stations in China - Tianran Han; Wang Tian; Yuheng Zhang; Jietao Zhou; Yanrong Yang; Keyu Chen; Lei Ren; Chuanfeng Wang; Yufei Huang; Haijiong Sun; Xinyi Chen; Chang Liu; et al. (Environmental Pollution, 2026)

Lithium-ion power batteries: From material performance to system-level safety and sustainability - Keyu Chen; JiaJia Luan; Brooke Xi; Weihua Zhang; Hanyu Jin; Daying Guo; Xi'’an Chen; Shun Wang (Chemical Engineering Journal, 2026)

Bacteria-inspired mechano-chemical nanovaccines enable multi-activation of dendritic cells for potent antitumor immunity - Hongjuan Zhao; Chenxi Zhao; Yuting Cang; Jinpei Sun; Qing Li; Keyu Zong; Yajing Wang; Di Meng; Qingling Song; Lei Wang (Chemical Engineering Journal, 2026)

Quantitative analysis of crust and loose layer characteristics on the surface of the earthen Great Wall - Keyu Wang; Wenwu Chen; Qiang Qi; Peiran Liu; Bobo Jia; Shuai Zhang; Quanquan Jia (CATENA, 2026)

Impacts of herbaceous plant roots on the engineering properties and erodibility assessment of the ming great wall earthen sites in the alpine and humid-cold regions - Qiang Qi; Wenwu Chen; Keyu Wang; Xiaoxiao He; Ying Wang; Fuqiang Liu; Shuai Zhang; Quanquan Jia (CATENA, 2026)

Heat transfer performance comparison and mechanism analysis of SCO2 and SCO2/R41 mixture in a double-pipe heat exchanger - Dong Wang; Keyu Sun; Hao Yu; Kangkang Zhang; Yinshuang Tao; Jun Shen (International Journal of Refrigeration, 2026)

Modification of Lycium ruthenicum pomace dietary fibers: Enhanced physicochemical, structural, and functional properties - Huiling Li; Keyu Tian; Ruiqi Wang; Ruyu Shangguan; Jingna Yang; Nana Yang; Xintao Meng; Xiang Li; Ting Zhang; Hongjie Lei (Food Chemistry, 2026)

Evolution of shale fracture systems in sedimentary basins: Constraints from multi-stage diagenetic processes and multi-field coupling - Junran Wang; Chao Liang; Tianyou Qin; Yingchang Cao; Keyu Liu; Fang Hao (Earth-Science Reviews, 2026)

Circadian-based individualised protection against inflammation–cancer transition in atrophic gastritis patients - Ceng Shan; Min Guo; Feifan Feng; Xihong Wang; Mohang Li; Weichao Xu; Keyu Jia; Yifei Liu; Yifan Jia (EPMA Journal, 2026)

Carbon isotope and mercury anomalies evidence across the Ordovician-Silurian boundary of volcanism accelerating the global carbon cycle - Haoran Xie; Chao Liang; Jing Wu; Yingchang Cao; Yu Han; Jiahong Wang; Keyu Liu; Fang Hao (Gondwana Research, 2026)

Numerical study on the dynamic characteristics of high-pressure hydrogen-oxygen premixed flame in combustion light gas gun - Junjie Lu; Qiuyang Zhao; Keyu Zhao; Tengyu Li; Yechun Wang; Hui Jin; Liejin Guo (Fuel, 2026)

Structural modifications triggered by environmental stress improve bioactivities of exopolysaccharide from endophytic bacterium Methylorubrum sp. Y19 of Taxus cuspidata - Junbo Liang; Xiaohan Zhang; Lin Zhu; Jing Luan; Keyu Sun; Jing Wang; Shuhong Ye (Food Bioscience, 2026)

Mineralization of calcium phosphate regulated by a Zr-based MOF on its surface for the removal of beryllium from Be-containing wastewater - Xu Zhao; Zhengyang Shan; Keyu Zhu; Yige Sun; Qingliang Wang; Xiujuan Feng (Chemical Engineering Journal, 2026)

Angstrom confined ion transport in graphene oxide membranes enables highly reversible zinc anodes - Lin Huang; Yihao Xu; Teng Deng; Shu Liu; Liping Chen; Yonghong Fu; Lei Dong; Juan Wang; Keyu Xie (Chemical Engineering Journal, 2026)

High-frequency redox fluctuations in deep-lacustrine basin and their impact on organic carbon burial: Records from micrometer-scale laminae in the Triassic Yanchang Formation Shale, Ordos Basin - Ke Li; Kelai Xi; Yingchang Cao; Zhe Zhao; Xiujuan Wang; Miruo Lin; Keyu Liu; Fang Hao (Science China Earth Sciences, 2026)

Corrigendum to “The hemolysin-associated TH locus in Vibrio mimicus reprograms central metabolism and couples it to oxidative stress defense through iron acquisition to drive virulence” Aquaculture, Volume 622, 15 July 2026, 744082 - Jiao Wang; Kun Peng; Yilin Wang; Keyu Zhou; Jingyi Lin; ping Ouyang; Xiaoli Huang; Defang Chen; Yi Geng (Aquaculture, 2026)

The hemolysin-associated TH locus in Vibrio mimicus reprograms central metabolism and couples it to oxidative stress defense through iron acquisition to drive virulence - Jiao Wang; Kun Peng; Yilin Wang; Keyu Zhou; Jingyi Lin; ping Ouyang; Xiaoli Huang; Defang Chen; Yi Geng (Aquaculture, 2026)

Formation of casein particles from decalcified micellar casein concentrate by simulating human milk mineral composition: Colloidal structures and in vitro digestibility in model infant formula emulsions - Keyu Wang; Wenzhu Yin; Xiumei Tao; Dasong Liu; Yaowei Liu; Hua Liu; Yimiao Wang; Thom Huppertz; Joe M. Regenstein; Xiaoming Liu; Peng Zhou (Food Hydrocolloids, 2026)

Transferable and adaptable full-field structural response reconstruction from sparse sensors via GraphSAGE–LSTM neural networks - Keyu Lai; Xiaoyou Wang; Yixian Li; Hong Guan; Yiming Zhang; Yong Xia (Engineering Structures, 2026)

Ankyrin-repeat transmembrane protein WAI-1 confers multiple disease resistance in wheat by activating autoimmunity - Qiuhong Wu; Wenling Li; Yongxing Chen; Huaizhi Zhang; Delin Li; Zhan Li; Fei Xiong; Guanghao Guo; Lei Dong; Xuejia Cui; Jingzhong Xie; Ping Lu; et al. (Science China Life Sciences, 2026)

Research on the ion-extraction demulsification mechanism and fiber-particle-induced coalescence for deep oil removal from high-salinity gas-field produced water - Haonan Liu; Keyu Wang; Yiqian Liu; Qiang Yang (Water Research, 2026)

Combining medium coalescence filtration and combined fiber coalescence: A pilot study on treating washing wastewater from shipboard EGR systems - Yu Li; Jinwei Xue; Guangyao Zhang; Yiqian Liu; Haonan Liu; Keyu Wang; Xin Han; Qiang Yang (Journal of Environmental Chemical Engineering, 2026)

Synergistic effects of pyrite and sludge biochar enhancing performance and reducing greenhouse gas emissions in constructed wetland-microbial fuel cells - Wang Maosen; Qin Yangyi; Wu Haiming; Zhao Jianguo; Zheng Lihe; Ding Keyu; Wang Baogui; Du Jingjing (Bioresource Technology, 2026)

Cerium-iron symbiotic nanozyme alleviates drought stress in wheat by targeting stomatal regulation and photosynthesis - Keyu Chen; Xiaowei Wang; Tao Yuan; Gehong Su; Chun Wu; Mengmeng Sun; Yanying Wang; Ming Hao; Xue Chen; Shiling Feng; Fuyong Wu; Dengcai Liu; et al. (Bioresource Technology, 2026)

Seismic-attribute optimization for improving reservoir prediction integrating the spectral decomposition and automated machine learning - Keyu Ren; Wei Li; Lun Zhao; Wurong Wang; Jincai Wang; Han Wang; Yi Li; Linbo Qu; Dali Yue (Journal of Applied Geophysics, 2026)

Larix gmelinii growth limitation shifts from nitrogen availability to drought under warming and permafrost degradation - Zecheng Chen; Binqing Zhao; Wenqi Song; Hans W. Linderholm; Jan Altman; Keyu Zhang; Hanjun Dong; Xinran Huang; Haoyuan Chen; Xiaochun Wang (Global and Planetary Change, 2026)

Maternal effects enhance offspring performance in the marine rotifer Brachionus plicatilis after exposure to BDE-47 and its photodegradation product BDE-28 - Na Lu; Chunchen Liu; Keyu Lu; Zhen Che; Boyuan Wang; You Wang; Yingying Yang (Journal of Oceanology and Limnology, 2026)

Opportunities to enhance sugarcane yield and gross margin under climate change through irrigation and planting date adaptation - Shijin Yao; De Li Liu; Bin Wang; Siyi Li; Jonathan K. Webb; Keyu Xiang; Alfredo Huete; Lihong Wu; Hao Quan; Qiang Yu (Irrigation Science, 2026)

RoofX-Net: A tailored approach to accurate multi-type rooftop segmentation in remote sensing images using edge and scale awareness - Keyu Chen; Tianlei Wang; Zhiyou Yang; Fan Li; Ma Luo; Ruoning Zhang; Hong Qu; Wenyu Chen (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

‘1347B’ module confers durable stripe rust resistance in wheat - Hongkui Fu; Delin Li; Huaizhi Zhang; Yongxing Chen; Ping Lu; Miaomiao Li; Gaojie Wang; Keyu Zhu; Lei Dong; Jian Yang; Chunhuan Chen; Bin Bai; et al. (Theoretical and Applied Genetics, 2026)

Developmental stage-specific disruption of iron allocation by a ZmYSL2 mutation in maize - Yikai Wang; Kunfeng Zhang; Chuang An; Jiayi Liu; Hongmei Hu; Duo Shi; Jiaxin Shi; Keyu Zhao; Dan Liu; Ling Wu; Xiao Zhang; Bowen Luo; et al. (Planta, 2026)

Differential microbial communities and metabolite profiles in the rhizosphere and bulk soils of rubber tree (Hevea brasiliensis) infected with red root rot disease - Xiangjia Meng; Haibin Cai; Yongwei Fu; Keyu Bai; Lifang Zou; Cuicui Wang; Yi Zhou; Min Tu (Plant and Soil, 2026)

Comprehensive chemical molecular characterization of petroleum-contaminated soils: Unraveling physical migration and biotransformation processes in the vadose and saturated zones - Wang Yu; Yuruo Wan; Jiuhao Song; Keyu Duan; Junjie Guan; Qi Gao; Yuping Zhang; Jianhui Ma; Jie Ma (Environmental Pollution, 2026)

Defect-triggered S-scheme heterojunction coupled with single-molecular catalytic centers towards selective photocatalytic CO2 reduction to CO - Keyu Cui; Yujia Wang; Xingjing Zhang; Jiaming Li; Chunbo Liu; Liqiu Zhang; Hongjun Dong; Chunmei Li (Chemical Engineering Journal, 2026)

Projecting shifts in drought-induced thresholds for wheat yield loss under climate change in southeastern Australia - Keyu Xiang; Bin Wang; De Li Liu; Chao Chen; Fei Ji; Fangzheng Chen; Shijin Yao; Siyi Li; Alfredo Huete; Yi Li; Qiang Yu (Agricultural and Forest Meteorology, 2026)

Apoptotic extracellular vesicles: unveiling mechanisms, diverse functions, and biomedical implications - Xuan Li; Keyu Wang; Caining Wen; Haorui Li; Limei Xu; Yuanmin Zhang; Xiao Xu; Yujie Liang (Apoptosis, 2026)

First Case of Nocardia seriolae Infection in China Cultured Channel Catfish ( Ictalurus punctatus ) - Mingqi Ai; Keyu Zhou; Qibin Jiang; Kun Peng; Yilin Wang; Yiteng Luo; Ping Ouyang; Defang Chen; Xiaoli Huang; Yi Geng (Journal of Fish Diseases, 2026)
Nocardia seriolae is a causative agent for fish skin ulcers and sarcoidosis, resulting in significant losses in both brackish and freshwater fish farming industries. From October to November 2023, channel catfishes ( Ictalurus punctatus ) cultured in Xiaowan reservoir at Dali city, Yunnan province in China, showed gross pathological changes with skin ulcers, white nodules in the liver and heart, histopathological tests revealed the typical granulomas and chronic hepatitis changes in the liver, and the clumps of filamentous bacteria in the heart and spleen. A Gram‐positive acid‐fast bacterium (CCF_NS01) was isolated from viscera (liver, spleen and kidney); biochemical tests and 16sRNA‐GyrB gene concatenated sequences analysis of this isolated microorganism identified it as N. seriolae . Drug sensitivity testing indicated susceptibility to commonly used antibiotics such as co‐trimoxazole, doxycycline, enrofloxacin, florfenicol, amikacin and rifampicin. In isolated CCF_NS01, multiple pathogenic factors corresponding to encoding genes were detected, including espG , mftF , pcaA , fadD32 , pks13 , narJ , feoB , sodA , katG and mceF . 100% mortality with 1 × 10 8 , 1 × 10 7 and 1 × 10 6 cfu/mL in a 35‐d challenge test period was observed, and the intraperitoneal injection median lethal dose (LD 50 ) was 1.89 × 10 4 cfu/mL. This is the first isolation report of N. seriolae infection from cultured channel catfish, aiming to warn against the continuous host‐range expansion of this pathogen, which is threatening the inland aquaculture industry.

Modelling the socio-ecological security pattern for large freshwater lake regions: supply-demand mismatch in the Dongting lake area - Zhenyu Wang; Yuhao Gong; Le Xia; Keyu Luo; Tao Jiang; Yi Ying; Miaomiao Xie (Environment, Development and Sustainability, 2026)

Synthetic data augmentation and Integrated prediction framework for low-carbon recycled concrete: Leveraging CTGAN and multiple ML models stacking - Jinlong Liu; Shiqi Wang; Keyu Chen; Kun Wang; Yucheng Fan; Qinghe Wang (Journal of Cleaner Production, 2026)

Future climate change increases the risk of wheat yield loss due to agricultural drought in southeastern Australia - Keyu Xiang; Bin Wang; De Li Liu; Chao Chen; Fei Ji; Shijin Yao; Siyi Li; Alfredo Huete; Yi Li; Qiang Yu (European Journal of Agronomy, 2026)

Smart optical imaging-assisted acoustic streaming enrichment system for targeted microalgae screening under multiple stress conditions - Yihan Ma; Longfei Chen; Yifan Wang; Tao Jiang; Chen Yang; Xiaotong Si; Yantong Liu; Keyu Chen; Fenghua Jiang; Chengjun Sun; Xuan Xiao; Yi Yang (Bioresource Technology, 2026)

Quantifying the effect of chlorite on reservoir quality and CO2 sequestration in deep saline aquifers from the permian tight sandstone reservoir in the ordos basin, China - Yaxin Shang; Keyu Liu; Ziyi Wang; Bo Zhang (Marine and Petroleum Geology, 2026)

Antisolvent sequence as a tunable switch for zein-naringin-D-tocopheryl polyethylene glycol 1000 succinate (TPGS) nanoparticles: interfacial dynamics and bioactivity enhancement - Yitong Wang; Keyu Qiu; Ruizi Zhou; Shuxian Bai; Chao Ai; Yanan Zhao; Jesus Simal-Gandara; Hui Teng; Lei Chen (Food Chemistry, 2026)

Unraveling the drivers of corn yield response to optimization fertilization in plateau acidic red soils - Zhengfa Chen; Keyu Yan; Hui Yan; Xiaohan Mei; Chi Wang; Xingwei Chen; Wanli Hu; Bin Fu; Ming Ni; Zhiwu Li; Qingsong Duan; Yanmei Hu; et al. (Field Crops Research, 2026)

Soft-chemical topotactic pathway to (001)-faceted hollandite K-Fe-Ti oxides with accelerated Li+ migration - Xing Wang; Ling Che; Zihao Li; Zhigao Chen; Xingang Kong; Kun Zhang; Keyu Xie (Chemical Engineering Journal, 2026)

ACSL4 Inhibition by AS-252424 Protects Visual Function by Suppressing RGC Ferroptosis After Retinal Ischemia Reperfusion Injury - Keyu Liu; Zihao Lin; Wu Xiang; Jiayi Zhang; Xiaofeng Wu; Chenzhao Ma; Yantao Wei; Jiawei Wang; Jianqiao Li (Molecular Neurobiology, 2026)

Climate warming enhances sugarcane yield and increases annual harvest frequency in northern coastal New South Wales, Australia - Shijin Yao; De Li Liu; Bin Wang; Jonathan K. Webb; Siyi Li; Alfredo Huete; Keyu Xiang; Qiang Yu (Agricultural Systems, 2026)

Modelling green space accessibility and equity in mountainous cities: a case study of Chongqing - Yuhan Wang; Keyu Luo; Zhenyu Wang; Meichen Fu (Environment, Development and Sustainability, 2025)

Responses of Phytoplankton Bloom Magnitude Off the Yangtze River Estuary to the Zonal Position of the Northwest Pacific Subtropical High - Qiong Wu; Keyu Hu; Bo Li; Tianqi Xiong; Hui Chen; Shaofeng Wang (International Journal of Climatology, 2025)
The phytoplankton bloom magnitude (PBM) off the Yangtze River Estuary has important responses to the changes in the east–west position of the northwest Pacific subtropical high (NWPSH). The potential physical mechanism is analyzed through observations and a physical–biogeochemical model. Results reveal that the anomalously high precipitation in June–July increases the extension ranges of low salinity and high NO 3 concentration water in NWPSH westward extension years. However, due to persistent cloudy and rainy weather, the light condition is unfavorable for the explosive growth of phytoplankton. When the NWPSH moves northward in August, the study area is controlled by anomalously anticyclonic circulation; hot and sunny weather prevails, the nutrients carried by the Yangtze River discharge during the previous June–July period continue to extend toward Jeju Island with the diluted water, favoring the explosive growth of phytoplankton, and vice versa. Sensitivity experiments reveal that when the June–July averaged river discharge and nutrients in NWPSH westward extension years are twice those in normal years, the range of phytoplankton blooms in August can extend to 124.2° E. When the June–July averaged river discharge and nutrients in NWPSH westward extension years are only 0.5 times those in normal years, the range of phytoplankton blooms in August only extends to 123° E. Therefore, the changes in river discharge and nutrient expansion range caused by the east–west position changes of the NWPSH in June–July are important reference indicators for phytoplankton bloom variations throughout the summer. The study provides new scientific reference for seasonal phytoplankton bloom forecasting off the Yangtze River Estuary.

Regional disparities and provincial peak trajectories of transportation carbon emissions in Western China - Zhixiao Zhang; Keyu Wen; Hao Gong; Yugang Wang; Liuhui Zhao; Dongmei Wang; Zhengjun Gong (Transportation Research Part D: Transport and Environment, 2025)

Exogenous melatonin regulates hormone metabolism involved in delaying the ripening process in cherry tomato fruit during storage - Hang Zhang; Yue Wang; Jianhui Cheng; Wenbo Lei; Keyu Xu; Lilai Yin; Chen Huan; Shuling Shen; Lanying Yao; Xiaolin Zheng (Postharvest Biology and Technology, 2025)

Integrated metabolomic and transcriptomic analysis to explore the mechanisms of ginkgo biloba leaf extract in controlling postharvest Penicillium expansum in sweet cherry - Keyu Sun; Ziwuzhen Wang; Shuhong Ye (Postharvest Biology and Technology, 2025)

Guttulatic calcite evidence for carboniferous icehouse climate in the Ordos Basin, North China Craton - Jiaqi Yang; Zhiliang He; Juntao Zhang; Keyu Liu; Macro Brandano; Jingbin Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Marine flooding induced basinal brine mixing and carbonate cementation: An example from Cretaceous ultra-deep clastic reservoirs in the Kuqa Depression, western China - Shunyu Wang; Jian Wang; Keyu Liu; Yong Li; Zhenkun Li; Meiyi Chen; Leilei Yang (Marine and Petroleum Geology, 2025)

Spatial accessibility to public electric vehicle charging infrastructure and multi-mechanism process of regional inequity in Greater Bay Area, China - Xing Gao; Huizi Wang; Ying Zhang; Keyu Zhai; Meiling Wu (Journal of Transport Geography, 2025)

Artificial perches improve the stability of soil microbial networks in degraded alpine steppe of Sanjiangyuan National Park - Yanhe Wang; Mingxin Yang; Keyu Chen; Dongzhi Huangqing; Shouxing Wang; Xiaochun Ning; Hongkui Yang; Qiang Gu; Huakun Zhou (Journal of Environmental Management, 2025)

Graphite-phase carbon nitride composites: Pioneering advancements and future prospects in capacitive desalination - Feifan Zhang; Hongying Lv; Yuying Pan; Yutao Chen; Keyu Hou; Zhiheng Wang; Jiuwen Sun; Hong Chen; Junli Pan; Shouqiang Huang (Journal of Environmental Management, 2025)

In vitro gastrointestinal digestibility under infant conditions of bovine milk fat emulsions stabilized using decalcified micellar casein concentrate - Keyu Wang; Yuhan Zhao; Wenzhu Yin; Dasong Liu; Xiumei Tao; Yimiao Wang; Thom Huppertz; Joe M. Regenstein; Xiaoming Liu; Peng Zhou (Food Hydrocolloids, 2025)

Thiol-functionalized dual network polysaccharide microgels for synergistic Patulin adsorption and gut-liver axis protection via delivery and controlled release of Ginkgo Biloba extract - Keyu Sun; Ziwuzhen Wang; Jiamin Jiang; Zilong Li; Shuhong Ye (Chemical Engineering Journal, 2025)

Delayed progression of diabetic cataractogenesis and retinopathy by topical administration of highly biocompatible carbon dots derived from Scutellaria barbata and Herba hedyotis diffusae - Jiawei Wang; Yihan Zhao; Xueying Yang; Can Li; Keyu Liu; Chenzhao Ma; Yanyan Jiang; Jianqiao Li (Chemical Engineering Journal, 2025)

Fingerprinting complex mixed oil spills at refineries: Source identification, quantitative source apportionment, and biodegradation assessment - Wang Yu; Jiayi An; Jiuhao Song; Junjie Guan; Keyu Duan; Wei Zhou; Liting Tian; Jie Ma (Water Research, 2025)

PRKAG1 mediates the anti-Japanese encephalitis virus effect of Nitazoxanide through autophagy - Hui Ma; Xiaoyang Wang; Chunmei Wang; Wenchong Ye; Wen Zhou; Fengcai Zou; Keyu Zhang (Veterinary Microbiology, 2025)

Efficacy of Ginkgo biloba extract in controlling patulin production by Penicillium expansum in sweet cherries - Keyu Sun; Ziwuzhen Wang; Shuhong Ye (Food Research International, 2025)

The synergistic effect of triazine-N and secondary amine-N anchors iodine species with MXene composite cathode for stable aqueous Zn–I2 battery - Jing Ma; Yaoyao Linghu; Kai Yuan; Rui Zhou; Hui Gao; Peihua Zhao; Shaohui Guo; Huiqi Wang; Yongping Qu; Chao Shen; Keyu Xie (Chemical Engineering Journal, 2025)

Abiotic stress-induced resveratrol accumulation in peanut sprouts: methods and research frontiers - Wangqi Zhang; Yihan Zhang; Shuang Wang; Keyu Wei; Shengdan Liu; Mouyan Liu; Huazhong Yu (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Dynamic quantitative characterization method for the weathering degree of earthen heritage sites surfaces based on 3D scanning technology and wavelet transform theory - Wenwu Chen; Qiang Qi; Keyu Wang; Shuai Zhang; Zhiqian Guo; Kebing Ren; Haitao Yan (Bulletin of Engineering Geology and the Environment, 2025)

Short-term emissions effect of rainfall erosion on soil CO2 in red soil sloped farmland in southern China - Keyu Yan; Xiaohan Mei; Chuan Zhang; Yanmei Hu; Daoxiang Wang; Zhengfa Chen; Xiaofeng Yang; Yanrui Shao; Yanjun Mao (Soil and Tillage Research, 2025)

Transgenerational effects and mechanisms of nano-SiO2 on pulmonary - Jiangliang Chu; Chengzhi Liu; Shuang Chen; Yifan Yang; Keyu Zhang; Yiping Fu; Beilei Yuan; Zhe Wang (Reproductive Toxicology, 2025)

Straw humification coefficient and its relation to soil carbon and nitrogen status - Yue Sun; Huiying Wang; Wei Jia; Keyu Ren; Bingjie Li; Hongqin Zou; Yinghua Duan; Minggang Xu (Journal of Environmental Management, 2025)

Sediment remediation by La-MOF/PP fabric coupled with phosphate solubilizing bacteria: Phosphate activation and removal - Qinqin He; Wenhao Lu; Hang Zhou; Xiaonan Ji; Wei Hu; Kuo Pang; Zedong Teng; Xin Zhao; Lintao Wang; Keyu Fan; Feichao Hu; Min Li (Journal of Environmental Chemical Engineering, 2025)

Brine shrimp cysts in the West Aral Sea from satellite observations - Keyu Mao; Lin Qi; Menghua Wang; Yao Yao; Ablatdiyn Musaev; Chuanmin Hu (International Journal of Remote Sensing, 2025)

Construction of sodium alginate/ginkgo biloba polysaccharide based films embedded with ginkgo biloba extract and its application in postharvest quality stabilization of sweet cherries - Keyu Sun; Ziwuzhen Wang; Wenxin Xiang; Shuhong Ye; Huiping Wan (Food Chemistry, 2025)

Bacillus altitudinis Q7 in alleviating postharvest abiotic stress of 'Nanguo' pears by modulating both respiratory and organic acid metabolism - Jing Wang; Yuke Liu; Keyu Sun; Shuhong Ye (Food Bioscience, 2025)

SiO2-assisted co-assembly of ultrafine aramid nanofiber-based porous thermal-resistant separator for Lithium-ion batteries - Fuhai Guo; Minghan Xu; Shi Feng; Keyu Zhang; Xiaotong Zheng; Hao Xue; Fulan Hao; Rui Zhuang; Qingchun Liu; Lei Zhang; Jianjun Zhang; Qingfu Wang (Chemical Engineering Journal, 2025)

Groundwater leakage of an endorheic basin with extensive permafrost coverage in the western Mongolian Plateau - Shun Hu; Cenhanyi Hu; Keyu Meng; Yinghui Long; Jing Zhang; Mingxin Wang; Linglin Zeng; Zilong Liao (Journal of Hydrology, 2025)

Detection of toluene at ppb levels using Au catalyst supported on Al-doped ZnO - Jiali Hong; Keyu Chen; Kaiping Yuan; Mingyue Lin; Qi Cao; Jialong Lin; XinLin Wang; Xiaoqian Bai; Tamao Ishida; Toru Murayama; Guangli Xiu (Journal of Environmental Chemical Engineering, 2025)

Performance and mechanism of enhanced phosphorus release and volatile fatty acid production from Fe-P sludge via co-fermenting with agricultural wastes - Wei Yao; Rongrong Chang; Keyu Chen; Chaoxi Yang; Yan Lu; Shixu Wang; Kaiyue Dong; Baocheng Huang; Rencun Jin (Journal of Environmental Sciences, 2025)

Regional NDVI reconstruction based on tree-ring width of Pinus massoniana Lamb. in the north-south transition zone of China - Kunyu Peng; Yameng Liu; Keyu Zhang; Jiaxin Li; Jinkuan Li; Xiaoxu Wei; Mengyu Wang; Jianfeng Peng (Dendrochronologia, 2025)

Multi-stage evolution of the Ordos Basin: Its coupled basin-mountain systems and energy resource - Yiwen Ju; Wei Wang; Zhanli Ren; Zhi Yang; Keyu Liu; Bing Hou; Lei Xiao (Science China Earth Sciences, 2025)

Climate change and social turmoil in the late Qing Dynasty revealed by tree rings - Jinkuan Li; Jiaxin Li; Yameng Liu; Keyu Zhang; Xiaoxu Wei; Mengyu Wang; Jianfeng Peng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

The potentials of uncertainty analysis and Bayesian optimization in HONO source modeling diagnosis and improvement - Jinlong Zhang; Wending Wang; Keyu Zhu; Zhijiong Huang; Li Sheng; Songdi Liao; Xin Yuan; Yanan Hu; Jiangping Liu; Mengxue Tang; Xiaofeng Huang; Jie Li; et al. (Environmental Research, 2025)

Nitrogen level determines arbuscular mycorrhizal fungi nitrogen uptake rate of Stipa purpurea in alpine steppe - Jiahui Sun; Yu Tang; Keyu Chen; Shijie Ren; Hailan Shi; Qiang Dong; Junfu Dong; Lin Zhang; Xiaoyong Cui; Yanfen Wang; Baoming Ji; Jing Zhang (Plant and Soil, 2025)

Activation of the Nrf2 Signaling Pathway by Tetrahydroberberine Suppresses Ferroptosis and Enhances Functional Recovery Following Spinal Cord Injury - Xiang Li; Heng Yu; Rongjie Liu; Jiansen Miao; Junlei Lv; Shu Yang; Yuxuan Zhu; Yan Chen; Keyu Lu; Chongan Huang; Xiangyang Wang (Molecular Neurobiology, 2025)

Impact of Proton Pump Inhibitors on Osimertinib-Induced Cardiotoxicity in NSCLC Patients - Haitao Wang; Sinan Ma; Weijia Huang; Keyu Chen; Jiao Xie; Na Wang; Youjia Li; Qianting Yang; Xin Yang; Yan Wang (Cardiovascular Toxicology, 2025)

Investigating the potential of magnesium isotopes in bioarchaeology: evidence from the Zaoshugounao Site - Keyu Liu; Xue Ling; Haifeng Dou; Yaopeng Qian; Zhen Wang; Yue Li; Kangjun Huang; Chunlei Zong (Archaeological and Anthropological Sciences, 2025)

Sensitive lateral flow immunoassay enabled by signal amplification strategy with high active oxidase-like nanozymes - Jie Zhu; Yunhui Cheng; Xufeng Wang; Hao Wu; Ye Jiao; Keyu Xing; Li Yao; Pei Jia; Zhou Xu (Food Bioscience, 2025)

Shanxioxylon yangquanense sp. nov., a new Kasimovian cordaitalean axis from the Benxi Formation (Pennsylvanian, Carboniferous) of Yangquan City, Shanxi Province, North China - Keyu Wang; Gaowen Jia; Liyang Dong; Jin Wang; Shijun Wang; Jun Wang; Mingli Wan (Review of Palaeobotany and Palynology, 2025)

Diagenetic controls on sweet spots pore types and reservoir quality of Permian tight sandstones in the Ordos Basin, China - Yaxin Shang; Keyu Liu; Ziyi Wang; Bo Zhang (Marine and Petroleum Geology, 2025)

Formation and control of heterocyclic amines and advanced glycation end products in traditional Chinese braised pork belly: The role of food additives - Keyu Lu; Qiaochun Chen; Jiayi He; Qian Zhou; Siqian Li; Mingfu Wang (Food Research International, 2025)

Corrigendum to “Gastrointestinal digestibility of micellar casein dispersions: Effects of caprine vs bovine origin, and partial colloidal calcium depletion using in vitro digestion models for the adults and elderly” [Food Chem. 416 (2023) 135865] - Jie Zhang; Dasong Liu; Yunqi Xie; Jiajie Yuan; Keyu Wang; Xiumei Tao; Yacine Hemar; Joe M. Regenstein; Xiaoming Liu; Peng Zhou (Food Chemistry, 2025)

Whether to continue combining carbapenems to treat carbapenem-resistant Acinetobacter baumannii nosocomial pneumonia in critically ill patients: a retrospective efficacy and safety analysis - Cheng Shiqi; Wang Chuhui; Zhang Yijing; Qiu Yulan; Chen Jiaojiao; Chen Keyu; Shi Qindong; Zeng Xiaoyan; Dong Yalin (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

How bedding-parallel fractures affect fluid activity in a relatively closed lacustrine shales system: Evidence from calcite veins - Zilong Li; Kelai Xi; Xiaobing Niu; Xiujuan Wang; Wenzhong Ma; Xiao Hui; Jiangyan Liu; Changyu Fan; Miruo Lin; Keyu Liu; Yingchang Cao (Marine and Petroleum Geology, 2025)

Soil with high plant available water capacity can mitigate the risk of wheat growth under drought conditions in southeastern Australia - Keyu Xiang; Bin Wang; De Li Liu; Chao Chen; Fei Ji; Yanmin Yang; Siyi Li; Mingxia Huang; Alfredo Huete; Qiang Yu (European Journal of Agronomy, 2025)

Thermally driven organic-inorganic interactions in sedimentary basins: A review from source rocks to reservoirs - Guanghui Yuan; Yingchang Cao; Zhijun Jin; Hans-Martin Schulz; Zihao Jin; Rui Fang; Xiaoyang Zhao; Keyu Liu; Jixuan Wang (Earth-Science Reviews, 2025)

Impact of landform on Spatial-Temporal distribution and Scenario-Based prediction of carbon stocks in arid Regions: A Case study of Xinjiang - Keyu Song; Weiming Cheng; Baixue Wang; Hua Xu (CATENA, 2025)

PAD resin: An intelligent adsorbent for solving Cr(VI) pollution with real-time feedback and high efficiency - Yuanhao Wang; Guihong Lan; Haiyan Qiu; Keyu Pu; Xiangming Liu; Ling Chen; Bo Xu (Journal of Hazardous Materials, 2025)

Cost effective selective separation of indium and germanium from zinc processing waste leach liquor using D2EHPA-YW100 synergistic system and selective stripping with HCl and NH4F - Chen Wang; Junxian Hu; Keyu Zhang; Shaoze Zhang; Yin Li; Yaochun Yao (Hydrometallurgy, 2025)

Ferric uptake regulator (Fur) in Vibrio mimicus acts as an activator of citrate cycle and oxidative phosphorylation pathways, while enhancing virulence potential - Kun Peng; Keyu Zhou; Qibin Jiang; Yilin Wang; Mingqi Ai; Le Xu; Jiao Wang; Ping Ouyang; Xiaoli Huang; Defang Chen; Yi Geng (Aquaculture, 2025)

Stability of China's terrestrial ecosystems carbon sink during 2000-2020 - Liang Shi; Honglin He; Li Zhang; Junbang Wang; Xiaoli Ren; Guirui Yu; Peng Hou; Jixi Gao; Bin Chen; Keyu Qin; Lili Feng; Shaoqiang Wang; et al. (Resources, Conservation and Recycling, 2025)

Disentangling and interpreting nonlinear molecular and isotopic variations in petroleum using machine learning - Keyu Tao; Jian Cao; Yuce Wang; Wanyun Ma (Marine and Petroleum Geology, 2025)

Mapping the susceptibility to freeze-thaw deterioration and regionalization of freeze-thaw environments of earthen sites in China: A preliminary study - Wenwu Chen; Keyu Wang; Qiang Qi; Bobo Jia; Ying Wang; Zhiqian Guo (Science of The Total Environment, 2024)

Coupled evolution of basin structure and fluids recorded by microfractures: A case study of deep-buried ordovician in the tarim basin - Jian Wang; Dongping Tan; Yingchang Cao; Jun Han; Haijun Yang; Yin Liu; Keyu Liu (Marine and Petroleum Geology, 2024)

Saline soil improvement promotes the transformation of microbial salt tolerance mechanisms and microbial-plant-animal ecological interactions - Keyu Yao; Guanghao Wang; Wen Zhang; Qiang Liu; Jian Hu; Mao Ye; Xin Jiang (Journal of Environmental Management, 2024)

Spatiotemporal changes and management measure to enhance ecosystem services in the Mongolian Plateau - Xianhua Wei; Xiaodong Wu; Dong Wang; Tonghua Wu; Ren Li; Guojie Hu; Defu Zou; Keyu Bai; Yadong Liu; Xuchun Yan; Xiaoying Fan; Avirmed Dashtseren; et al. (Environmental Development, 2024)

The modulation of proteomics and antioxidant stress is involved in the effect of nitazoxanide against Japanese encephalitis virus in vitro - Yu Su; Yanping Wang; Chengeng Xiong; Xiaoyang Wang; Chunmei Wang; Wen Zhou; Donghai Zhou; Keyu Zhang (Veterinary Microbiology, 2024)

Eco-friendly synthesis of silver nanoparticles against mosquitoes: Pesticidal impact and indispensable biosafety assessment - Chunzhi Wang; Yang Jiang; Keyu He; Yán Wāng (Science of The Total Environment, 2024)

Optimizing pollen germination and subcellular dynamics in pollen tube of Torreya grandis - Shuai Hu; Chengqiao Wang; Rui Zhang; Yanli Gao; Keyu Li; Jinbo Shen (Plant Science, 2024)

Authigenic calcite in shales: Implications for tracing burial processes and diagenetic fluid evolution in sedimentary basins - Chao Liang; Junran Wang; Yingchang Cao; Zhouhai Xiong; Keyu Liu; Fang Hao; Wanlu Han (Earth-Science Reviews, 2024)

LNP-mRNA delivers TNF-α antibody to deep cartilage and protects against osteoarthritis - Baixing Li; Lei Cui; Keyu Kong; Yichuan Pang; Yan Chen; Shuning Zhang; Fangfang Wang; Tangjun Zhou; Yunfeng Hua; Mi Cao; Hongtao Xu; An Qin; et al. (Chemical Engineering Journal, 2024)

Development of a CRISPR/Cas12a-based method to detect invasive aquatic species - Minlin Zhang; Xiaoling Zuo; Jiantao Liang; Keyu Lu; Liyun Wei; Xu Yan; Huihong Zhao; Songyong Gan; Jinhui Wu; Qing Wang (Aquaculture, 2024)

Petaloid CoP/FeP Composites: Efficiently bifunctional cathode electrochemical oxygen catalysts for aqueous and Solid-State Zinc-Air batteries - Keyu Chen; Lu Wang; Jilan Long; Fei Zhao; Li Kang (Chemical Engineering Journal, 2024)

Isolation of a facultative methanotroph Methylocystis iwaonis SD4 from rice rhizosphere and establishment of rapid genetic tools for it - Yinghui Wang; Yuying Wang; Keyu Zhou; Haili Zhang; Minggen Cheng; Baozhan Wang; Xin Yan (Biotechnology Letters, 2024)

Unleashing hidden carbon sequestration potential: A case study of the Greater Bay Area, China - Keyu Luo; Zhenyu Wang; Weifeng Li; Jiansheng Wu (Urban Climate, 2024)

Effects of seasoning addition and cooking conditions on the formation of free and protein-bound heterocyclic amines and advanced glycation end products in braised lamb - Qiaochun Chen; Keyu Lu; Jiayi He; Qian Zhou; Siqian Li; Hui Xu; Yuting Su; Mingfu Wang (Food Chemistry, 2024)

Protocupressinoxylon baii sp. nov., a gymnospermous fossil trunk from the Upper Shihhotse Formation (Permian) of Yangquan City, Shanxi Province, North China - Kaige Jiang; Keyu Wang; Jun Wang; Mingli Wan (Review of Palaeobotany and Palynology, 2024)

Advancements in smart building envelopes: A comprehensive review - Guanqun Wang; Junjian Fang; Chengchu Yan; Dehai Huang; Kai Hu; Keyu Zhou (Energy and Buildings, 2024)

Germ cell-specific gene 2 accelerates cell cycle in epithelial ovarian cancer by inhibiting GSK3α-p27 cascade - Keyu Zhu; Xiaolu Ma; Xiaolin Guan; Ying Tong; Suhong Xie; Yanchun Wang; Hui Zheng; Lin Guo; Renquan Lu (Journal of Molecular Histology, 2024)
Epithelial ovarian cancer (EOC) is one of the most common malignant gynecological tumors with rapid growth potential and poor prognosis, however, the molecular mechanism underlying its outgrowth remained elusive. Germ cell-specific gene 2 (GSG2) was previously reported to be highly expressed in ovarian cancer and was essential for the growth of EOC. In this study, GSG2-knockdown cells and GSG2-overexpress cells were established through lentivirus-mediated transfection with Human ovarian cancer cells HO8910 and SKOV3. Knockdown of GSG2 inhibited cell proliferation and induced G2/M phase arrest in EOC. Interestingly, the expression of p27, a well-known regulator of the cell cycle showed a most significant increase after GSG2 knockdown. Further phosphorylation-protein array demonstrated the phosphorylation of GSK3αSer21 decreased in GSG2-knockdown cells to the most extent. Notably, inhibiting GSK3α activity effectively rescued GSG2 knockdown’s suppression on cell cycle as well as p27 expression in EOC. Our study substantiates that GSG2 is able to phosphorylate GSK3α at Ser21 and then leads to the reduction of p27 expression, resulting in cell cycle acceleration and cell proliferation promotion. Thus, GSG2 may have the potential to become a promising target in EOC.

Frond characteristics of Cyrillopteris (ex. Odontopteris) orbicularis (Halle) comb. et emend. nov.: New evidence from the Permian Upper Shihezi (Upper Shihhotse) Formation of North China - Mingli Wan; Dandan Li; Shan Wan; Wan Yang; Weiming Zhou; Keyu Wang; Kaige Jiang; Jun Wang (Review of Palaeobotany and Palynology, 2024)

Fluid tracing and evolution at micron-scale of shales in faulted lake basin: Evidence and constraints from in-situ analysis of analcime - Junran Wang; Chao Liang; Yingchang Cao; Shunyao Song; Keyu Liu; Shengyu Yang; Jinqiang Tian; Danish Khan; Bixiao Xin (Marine and Petroleum Geology, 2024)

Occurrence of ochratoxin A in Sichuan bacon from different geographical regions and characterization and biocontrol of ochratoxigenic Aspergillus westerdijkiae strain 21G2-1A - Kaidi Hu; Keyu Guo; Xingjie Wang; Song Wang; Jianlong Li; Qin Li; Ning Zhao; Aiping Liu; Li He; Xinjie Hu; Yong Yang; Likou Zou; et al. (Food Research International, 2024)

Effect of hydrothermal carbonization on pyrolysis behavior, nutrients and metal species distribution in municipal sludge - Changhao Liu; Zhengbo Yue; Ding Ma; Keyu Li; Zhilin Xie; Tianqin Zhang; Jin Wang (Bioresource Technology, 2024)

Effects of natural extract from medicinal herbs on broilers experimentally infected with Eimeria tenella - Yuanyuan Jiang; Yujuan Zeng; Keyu Chen; Haoran Cheng; Songjiang Dai; Xuexue Deng; Long Wang; Jinqiu Liao; Ruiwu Yang; Li Zhang (Veterinary Parasitology, 2024)

Integration of hydrothermal liquefied sludge as wastewater for anaerobic treatment and energy recovery: Aqueous phase characterization, anaerobic digestion performance and energy balance analysis - Changhao Liu; Zhengbo Yue; Ding Ma; Keyu Li; Pengcheng Zhao; Manyi Yang; Jin Wang (Journal of Water Process Engineering, 2024)

The relationship between repeated impacts and CAI strength of sandwich structure considering different impactor shape in individual impact - Keyu Zhu; Xitao Zheng; Jiaming Sun; Guoyue Wang; Leilei Yan (Engineering Structures, 2024)

Moderate grazing increased carbon, nitrogen and phosphorus storage in plants and soil in the Eurasian meadow steppe ecosystem - Miao Wang; Chu Zhang; Sisi Chen; Yu Zhang; Tianqi Yu; Xiaojuan Xue; Lianhai Wu; Wenneng Zhou; Xiangjun Yun; Ruirui Yan; Keyu Bai (Science of The Total Environment, 2024)

Multi objective optimization of recycled aggregate concrete based on explainable machine learning - Shiqi Wang; Peng Xia; Fuyuan Gong; Qiang Zeng; Keyu Chen; Yuxi Zhao (Journal of Cleaner Production, 2024)

Application of nisin-embedded pectin microcapsules for ‘Guiqi’ mango fruit postharvest preservation - Wenqing Liu; Keyu Huang; Zhimei Tan; Chenshu Wang; Tongquan Wen; Liyuan Huang; Fangxue Hang; Caifeng Xie; Shupei Wang; Kai Li (Food Packaging and Shelf Life, 2024)

The fundamentals, progress, and perspectives of transition-metal dichalcogenides (TMDs) applied in advanced oxidation processes - Hao Huang; Mengyang Zhang; Keyu Xu; Yanling Zhuang; Yue Li; Longlu Wang (Chemical Engineering Journal, 2024)

Comparison analysis of microbial agent and different compost material on microbial community and nitrogen transformation genes dynamic changes during pig manure compost - Naiyuan Liu; Zhuangzhuang Liu; Keyu Wang; Jinfeng Zhao; Jun Fang; Gang Liu; Hao Yao; Junting Pan (Bioresource Technology, 2024)

Investigation on catalytic distillation dehydrogenation of perhydro-benzyltoluene: Reaction kinetics, modeling and process analysis - Qinglian Wang; Keyu Le; Yi Lin; Wang Yin; Yixiong Lin; Maria V. Alekseeva; Vadim A. Yakovlev; Anton P. Koskin; Chen Yang; Ting Qiu (Chemical Engineering Journal, 2024)

Ibuprofen inhibits anaplastic thyroid cells in vivo and in vitro by triggering NLRP3-ASC-GSDMD-dependent pyroptosis - Haohao Guo; Runsheng Ma; Yifei Zhang; Keyu Yin; Gongbo Du; Fanxiang Yin; Hongqiang Li; Ziyang Wang; Detao Yin (Inflammopharmacology, 2024)
Pyroptosis is a novel type of proinflammatory programmed cell death that is associated with inflammation, immunity, and cancer. Anaplastic thyroid carcinoma (ATC) has a high fatality rate, and there is no effective or standard treatment. The disease progresses rapidly and these tumors can invade the trachea and esophagus, leading to breathing and swallowing difficulties. Hence, new treatment methods are greatly needed. Ibuprofen is a common drug that can exert antitumor effects in some cancers. In this study, we demonstrated in vitro and in vivo that ibuprofen can induce ATC pyroptosis. Hence, we treated C643 and OCUT-2C ATC cells with ibuprofen and found that several dying cells presented the characteristic morphological features of pyroptosis, such as bubble-like swelling and membrane rupture, accompanied by activation of ASC and NLRP3 and cleavage of GSDMD. Along with the increased release of LDH, ibuprofen treatment promoted apoptosis and inhibited viability, invasion, and migration. However, overexpression of GSDMD significantly inhibited ibuprofen-induced pyroptosis. In vivo, research has demonstrated that thyroid tumor growth in nude mice can be suppressed by ibuprofen-induced pyroptosis in a dose-dependent manner. In this research, we explored a new mechanism by which ibuprofen inhibits ATC growth and progression and highlighted its promise as a therapeutic agent for ATC.

How does grazing pressure affect feed intake and behavior of livestock in a meadow steppe in northern China and their coupling relationship - Tianqi Yu; Ruirui Yan; Chu Zhang; Sisi Chen; Zhitao Zhang; LeiFeng Guo; Tianci Hu; Chengxiang Jiang; Miao Wang; Keyu Bai; Wenneng Zhou; Lianhai Wu (Science of The Total Environment, 2024)

The influence of asphaltene matrix on the thermal evolution of polycyclic aromatic hydrocarbons: Experimental evidence and geochemical implications - Peng Fang; Zhibin Hong; Jia Wu; Yuan Wang; Keyu Liu; Minghui Zhou (Journal of Asian Earth Sciences, 2024)

The boundary between the Middle and Upper Cambrian strata in the Tarim Basin, NW China: Regional to global SPICE event correlation - Yaxin Shang; Keyu Liu; Zhiqian Gao; Chenjia Zhang; Ziyi Wang (Journal of Asian Earth Sciences, 2024)

Stochastic and deterministic assembly processes of bacterial communities in different soil aggregates - Yan Wang; Kun Zhu; Xin Chen; Keyu Wei; Rong Wu; Gang Wang (Applied Soil Ecology, 2024)

Selective efficient photocatalytic degradation of antibiotics and direct Z-type migration pathway for hierarchical core–shell TiO2/g-C3N4 composites - Hu Liu; Jianmei Pan; Keyu E; Yi Guan; Wenbo Gou; Peng Wang; Shahid Hussain; Ze Du; Chengfei Ma (Environmental Science and Pollution Research, 2023)

Revealing the infiltration process and retention mechanisms of surface applied free DNA tracer through soil under flood irrigation - Geng Liu; Linxi Guo; Chaozi Wang; Jiarong Liu; Zengjie Hu; Helen E. Dahlke; En Xie; Xiao Zhao; Guanhua Huang; Jun Niu; Keyu Fa; Chenglong Zhang; et al. (Science of The Total Environment, 2023)

Where does floating Sargassum in the East China Sea come from? - Lin Qi; Peng Cheng; Menghua Wang; Chuanmin Hu; Yuyuan Xie; Keyu Mao (Harmful Algae, 2023)

Revealing continuous hydrocarbon generation and shale oil accumulation of saline lacustrine source rocks by sequential extraction - Wenwen Li; Jian Cao; Wenxuan Hu; Yong Tang; Baoli Xiang; Wanyun Ma; Wenjun He; Keyu Tao; Yingqi Wang (Fuel, 2023)

Discovery of a heterotrophic aerobic denitrification Pseudomonas sp. G16 and its unconventional nitrogen metabolic pathway - Yu Gao; Junwen Zhu; Keyu Wang; Yong Ma; Jun Fang; Gang Liu (Bioresource Technology, 2023)

Geochemistry of syntaxial calcite veins in ultra-deep sandstone reservoirs from the Kuqa depression, western China - Shunyu Wang; Keyu Liu; Jian Wang; Yong Li; Zhenkun Li; Haijun Yang; Tao Mo (Journal of Structural Geology, 2023)

Gastrointestinal digestibility of micellar casein dispersions: Effects of caprine vs bovine origin, and partial colloidal calcium depletion using in vitro digestion models for the adults and elderly - Jie Zhang; Dasong Liu; Yunqi Xie; Jiajie Yuan; Keyu Wang; Xiumei Tao; Yacine Hemar; Joe M. Regenstein; Xiaoming Liu; Peng Zhou (Food Chemistry, 2023)

Achieving high yield and nitrogen agronomic efficiency by coupling wheat varieties with soil fertility - Keyu Ren; Minggang Xu; Rong Li; Lei Zheng; Huiying Wang; Shaogui Liu; Wenju Zhang; Yinghua Duan; Changai Lu (Science of The Total Environment, 2023)

Mixing processes and patterns of fluids in alkane-CO2-water systems under high temperature and high pressure—Microscopic visual physical thermal simulations and molecular dynamics simulations - Guanghui Yuan; Shuqi Wu; Yingchang Cao; Zihao Jin; Keyu Liu; Yanzhong Wang (Science China Earth Sciences, 2023)

The influence of CO2 partial pressure on the stability of dawsonite-based on water-rock physical experiment and numerical simulation - Fulai Li; Chun Zhang; Kaining Wang; Wenkuan Ma; Jianlei Yang; Qizhen Du; Shaogui Deng; Keyu Liu (Applied Geochemistry, 2023)

The characteristics and metabolic potentials of the soil bacterial community of two typical military demolition ranges in China - Keyu Yao; Anjuan Cai; Jin Han; Ruijie Che; Jiarong Hao; Fenghe Wang; Mao Ye; Xin Jiang (Science of The Total Environment, 2023)

Decalcification strongly affects in vitro gastrointestinal digestion of bovine casein micelles under infant, adult and elderly conditions - Keyu Wang; Dasong Liu; Xiumei Tao; Jie Zhang; Thom Huppertz; Joe M. Regenstein; Xiaoming Liu; Peng Zhou (Food Hydrocolloids, 2023)

Identification of the chemical constituents in Cullen corylifolium ethanolic extract by LC-MS/MS and GC-MS - Hongzheng Wang; Keyu Chen; Rui Xue; Chimengul Turghun; Bo Han (Natural Product Research, 2023)

A new gymnospermous stem from the Moscovian (Carboniferous) of North China, and its palaeoecological significance for the Cathaysian Flora at the early evolutionary stage - Keyu Wang; Xing Huang; Wan Yang; Jun Wang; Mingli Wan (Review of Palaeobotany and Palynology, 2023)

Spatiotemporal variations and driving factors for potential wind erosion on the Mongolian Plateau - Xianhua Wei; Xiaodong Wu; Dong Wang; Tonghua Wu; Ren Li; Guojie Hu; Defu Zou; Keyu Bai; Xin Ma; Yadong Liu; Xuchun Yan; Xiaoying Fan; et al. (Science of The Total Environment, 2023)

A systematic review and meta-analysis of air pollution and angina pectoris attacks: identification of hazardous pollutant, short-term effect, and vulnerable population - Min Yang; Keyu Wu; Qiyue Wu; Cunrui Huang; Zhiwei Xu; Hung Chak Ho; Junwen Tao; Hao Zheng; Mohammad Zahid Hossain; Wenyi Zhang; Ning Wang; Hong Su; et al. (Environmental Science and Pollution Research, 2023)

A three-dimensional experimental study on bank retreat: The coupled role of seepage and surface flow - Keyu Wang; Zheng Gong; Kun Zhao; Shuai Tang; Kaili Zhang (Frontiers in Marine Science, 2022)
The coupled role of seepage and surface flow on bank retreat has long been neglected, partly due to the concealment and complexity of seepage erosion. To fill this gap, we set up a three-dimensional laboratory experiment to explore bank retreat process in response to seepage and surface flow. During each experiment, we measured the changes of total soil stress, matric suction, and water content within the bank, as well as flow velocity and suspended sediment concentration near the bank. Results show that a rapid decrease in matric suction, the bank toe undercutting consequent to seepage erosion, the formation of tension crack on the bank top, and the occurrence of toppling or shear failure is the typical sequence of the observed bank retreat process under seepage flow. The inclusion of surface flow erodes slump blocks and so promotes cantilever formation, leading to additional bank failure. Compared with the case where only seepage is considered, the frequency of toppling failure under the coupled effect of seepage and surface flow decreases, but the contribution to the bank retreat increases by 37 %. The time taken to collapse in three-dimensional experiments is at least 1.5 h earlier than that of two-dimensional experiments, indicating the importance of preferential flow pathways of seepage. Overall, this research illustrates how surface flow interacts with seepage flow to control bank retreat process and is indeed a first step toward a fully understanding of multifactor-driven bank retreat.

Successive formation of secondary pores via feldspar dissolution in deeply buried feldspar-rich clastic reservoirs in typical petroliferous basins and its petroleum geological significance - Yingchang Cao; Guanghui Yuan; Yanzhong Wang; Nianmin Zan; Zihao Jin; Keyu Liu; Kelai Xi; Yihan Wei; Peipei Sun (Science China Earth Sciences, 2022)

A comprehensive review of the circulation of microplastics in aquatic ecosystem using scientometric method - Yuan Gao; Keyu Fan; Zini Lai; Chao Wang; Haiyan Li; Qianfu Liu (Environmental Science and Pollution Research, 2022)

Fine mapping of powdery mildew resistance gene MlWE74 derived from wild emmer wheat (Triticum turgidum ssp. dicoccoides) in an NBS-LRR gene cluster - Keyu Zhu; Miaomiao Li; Haibin Wu; Deyun Zhang; Lingli Dong; Qiuhong Wu; Yongxing Chen; Jingzhong Xie; Ping Lu; Guanghao Guo; Huaizhi Zhang; Panpan Zhang; et al. (Theoretical and Applied Genetics, 2022)

Interactions between hydrocarbon-bearing fluids and calcite in fused silica capillary capsules and geological implications for deeply-buried hydrocarbon reservoirs - Zihao Jin; Guanghui Yuan; Yingchang Cao; Keyu Liu; Yanzhong Wang; Jianye Sun; Xiluo Hao; Ling Zhou; Yihan Wei; Shuqi Wu (Science China Earth Sciences, 2022)

Revisiting Rhenium-Osmium Isotopic Investigations of Petroleum Systems: From Geochemical Behaviours to Geological Interpretations - Shao-Jie Li; Xuan-Ce Wang; Simon A. Wilde; Zhuyin Chu; Chaofeng Li; Sheng He; Keyu Liu; Xingzhi Ma; Yuxiang Zhang (Journal of Earth Science, 2021)

Impact of chlorites on the wettability of tight oil sandstone reservoirs in the Upper Triassic Yanchang Formation, Ordos Basin, China - Zhongnan Wang; Xiaorong Luo; Keyu Liu; Yuchen Fan; Xiangzeng Wang (Science China Earth Sciences, 2021)

Optimized production and characterization of cation-independent bioflocculant produced by Klebsiella sp. 59L - Keyu Fang; Boji Wang; Yao Zhang; Hongjing Li (Environmental Science and Pollution Research, 2021)

Multi-model ensemble simulated non-point source pollution based on Bayesian model averaging method and model uncertainty analysis - Huiliang Wang; Keyu Lu; Yulong Zhao; Jinxia Zhang; Jianli Hua; Xiaoying Lin (Environmental Science and Pollution Research, 2020)

Identification and fine mapping of spot blotch (Bipolaris sorokiniana) resistance gene Sb4 in wheat - Panpan Zhang; Guanghao Guo; Qiuhong Wu; Yongxing Chen; Jingzhong Xie; Ping Lu; Beibei Li; Lingli Dong; Miaomiao Li; Rongge Wang; Chengguo Yuan; Huaizhi Zhang; et al. (Theoretical and Applied Genetics, 2020)

Roles of sulfur compounds in growth and alkaline phosphatase activities of Microcystis aeruginosa under phosphorus deficiency stress - En Xie; Fangfang Li; Chaozi Wang; Wei Shi; Chen Huang; Keyu Fa; Xiao Zhao; Dayi Zhang (Environmental Science and Pollution Research, 2020)

Identified trans-splicing of YELLOW-FRUITED TOMATO 2 encoding the PHYTOENE SYNTHASE 1 protein alters fruit color by map-based cloning, functional complementation and RACE - Lulu Chen; Wenzhen Li; Yongpeng Li; Xuechao Feng; Keyu Du; Ge Wang; Lingxia Zhao (Plant Molecular Biology, 2019)

Correction to: Cellular distribution of cadmium in two amaranth (Amaranthus mangostanus L.) cultivars differing in cadmium accumulation - Keyu Chi; Rong Zou; Li Wang; Wenmin Huo; Hongli Fan (Environmental Science and Pollution Research, 2019)

Cellular distribution of cadmium in two amaranth (Amaranthus mangostanus L.) cultivars differing in cadmium accumulation - Keyu Chi; Rong Zou; Li Wang; Wenmin Huo; Hongli Fan (Environmental Science and Pollution Research, 2019)

Construction of a small-caliber tissue-engineered blood vessel using icariin-loaded β-cyclodextrin sulfate for in situ anticoagulation and endothelialization - Jingyuan Yang; Keyu Wei; Yeqin Wang; Yanzhao Li; Ning Ding; Da Huo; Tianran Wang; Guanyuan Yang; Mingcan Yang; Tan Ju; Weng Zeng; Chuhong Zhu (Science China Life Sciences, 2018)

Identification of long non-coding RNA p34822 as a potential plasma biomarker for the diagnosis of hepatocellular carcinoma - Cheng Wang; Tianyu Ren; Keyu Wang; Shaogeng Zhang; Shubin Liu; Hu Chen; Penghui Yang (Science China Life Sciences, 2017)

Taking climate, land use, and social economy into estimation of carbon budget in the Guanzhong-Tianshui Economic Region of China - Ting Li; Jing Li; Zixiang Zhou; Yanze Wang; Xiaonan Yang; Keyu Qin; Jingya Liu (Environmental Science and Pollution Research, 2017)

Analysis of S1 gene of avian infectious bronchitis virus isolated in southern China during 2011–2012 - Keyu Feng; Yu Xue; Feng Wang; Feng Chen; Dingming Shu; Qingmei Xie (Virus Genes, 2014)